PERKEMBANGAN ISLAM DI INGGRIS - S, Nuraeni (Al-Hikmah, 2019)
Islam entered the United Kindom with the presence of individual contacts of British society with the Islamic community, and the existence of a group of Muslims who came to trade, as well as workers in the United Kindom. Until now there are around 2,869,000 Muslims in the United Kindom or 4.6 percent of the total population. This number jumped far from the 2001 census which only recorded 1,677,000 Muslims. Islamic organizations in Britain have given their own color to the development of Islam, these organizations have at least opened the eyes of the British about Islamic matters, which they do openly and interact with non-Muslim English people.